Microsoft Security, Compliance, and Identity Fundamentals Exam Ref SC-900 : Familiarize Yourself with Security, Identity, and Compliance in Microsoft 365 and Azure - Natwick, Dwayne (Packt Publishing, Limited, 2022)
Understand the fundamentals of security, compliance, and identity solutions across Microsoft Azure, Microsoft 365, and related cloud-based Microsoft services Key Features Grasp Azure AD services and identity principles, secure authentication, and access management Understand threat protection with Microsoft 365 Defender and Microsoft Defender for Cloud security management Learn about security capabilities in Microsoft Sentinel, Microsoft 365 Defender, and Microsoft Intune Book Description Cloud technologies have made building a defense-in-depth security strategy of paramount importance. Without proper planning and discipline in deploying the security posture across Microsoft 365 and Azure, you are compromising your infrastructure and data. Microsoft Security, Compliance, and Identity Fundamentals is a comprehensive guide that covers all of the exam objectives for the SC-900 exam while walking you through the core security services available for Microsoft 365 and Azure. This book starts by simplifying the concepts of security, compliance, and identity before helping you get to grips with Azure Active Directory, covering the capabilities of Microsoft's identity and access management (IAM) solutions. You'll then advance to compliance center, information protection, and governance in Microsoft 365. You'll find out all you need to know about the services available within Azure and Microsoft 365 for building a defense-in-depth security posture, and finally become familiar with Microsoft's compliance monitoring capabilities. By the end of the book, you'll have gained the knowledge you need to take the SC-900 certification exam and implement solutions in real-life scenarios. What you will learn Become well-versed with security, compliance, and identity principles Explore the authentication, access control, and identity management capabilities of Azure Active Directory Understand the identity protection and governance aspects of Azure and Microsoft 365 Get to grips with the basic security capabilities for networks, VMs, and data Discover security management through Microsoft Defender for Cloud Work with Microsoft Sentinel and Microsoft 365 Defender Deal with compliance, governance, and risk in Microsoft 365 and Azure Who this book is for This book is for cloud security engineers, Microsoft 365 administrators, Azure administrators, and anyone in between who wants to get up to speed with the security, compliance, and identity fundamentals to achieve the SC-900 certification. A basic understanding of the fundamental services within Microsoft 365 and Azure will be helpful but not essential.